The reproductive implications of clomiphene citrate on sperm cells during the epididymal transit of spermatozoa in male wistar rats (2006)
The reproductive implications of Clomiphene citrate (CC) on male Wistar rats revealed the reactions of the rats to CC at different dosages (varied). Results revealed detrimental effects at a higher dosage. In the caput of the epididymidis, the mean percentage motility in group B Wistar rats (20.0 ±8.66) and group C Wistar rats (23.3 ±3.33) was significantly lower (P<0.05) than group A Wistar rats (42.0 ± 2.00). The drug did not influence the percentage livability of the spermatozoa in the caput epididymidis. In the corpus epididymis the mean percentage motility for groups A — C were 56.00 ±2.45, 25.56 ±7.50, 13.00 ±5.77, respectively. Group A value was significantly higher than those of groups B and C. The percentage livability was higher in-group A than B and C. The concentration of the spermatozoa was significantly higher in group A (78.25 ±6.97. 106) than groups B (53.75 ±1.89. 106), though this is not significantly different (P<0.05). These findings were discussed in relation to the significance of the drug as a fertility enhancer in infertile animals. The reproductive implications of the drug were studied in the epididymis of Wistar rats with no adverse effects when used at the recommended dose. The drug can therefore be used to boost the reproductive potential of infertile male animals.